2011
DOI: 10.1111/j.1755-3768.2009.01683.x
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in anterior chamber depth in primary open‐angle glaucoma patients during latanoprost therapy

Abstract: ABSTRACT.Purpose: The aim of this study was to evaluate changes in the anterior chamber depth (ACD) in primary open-angle glaucoma (POAG) patients during latanoprost therapy. Methods: We carried out a prospective study in which we enrolled 66 newly diagnosed POAG patients treated with latanoprost 0.005% (group 1) and 50 ocular hypertensive and ⁄ or glaucoma suspect cases who were given no therapy (group 2 [control]). Measurements of the ACD were performed by A-scan ultrasonography before and after cycloplegia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 18 publications
0
6
1
Order By: Relevance
“…We measured these parameters before antiglaucoma treatment and excluded patients with previous anti-glaucoma treatment because these agents may affect the structure of the anterior segment. 17,18…”
Section: Discussionmentioning
confidence: 99%
“…We measured these parameters before antiglaucoma treatment and excluded patients with previous anti-glaucoma treatment because these agents may affect the structure of the anterior segment. 17,18…”
Section: Discussionmentioning
confidence: 99%
“…The main purpose of our study was to investigate the alterations in anterior chamber depth (ACD) during latanoprost 0.005% therapy and whether these alterations were influenced by the effect of cyclopentolate. In our study, latanoprost was found to have a decreasing effect on ACD in eyes both with and without cycloplegia (Cankaya et al. 2011).…”
mentioning
confidence: 48%
“…We thank Drs Gutierrez‐Ortiz C and Teus M (2011) for their interest in our article (Cankaya et al. 2011) and note their concern regarding the possible misinterpretation of our findings.…”
mentioning
confidence: 90%
“…Cankaya et al. (2011) speculate that their finding that cycloplegia deepened the anterior chamber to the same extent after latanoprost therapy than in virgin eyes rules out that latanoprost‐induced weakening in the zonular fibres may be present.…”
mentioning
confidence: 99%
“…We have read, with interest, the paper recently published in Acta Ophthalmologica by Cankaya et al. (2011).…”
mentioning
confidence: 99%